Analisis Kinerja Database Dalam Sistem E-Commerce - Dea Cindi Amelia; Ginting Ginting; Muhammad Irwan Padli Nasution (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2023)
E-commerce or electronic commerce is growing rapidly with advances in technology. The database is one of the main components in the E-commerce system which functions to store transaction data and customer information. Therefore, analysis of database performance on E-commerce systems is very important to ensure data availability and reliability. This study is intended to analyze database performance on E-commerce systems. The method used is a literature study conducted to gain a better understanding of the basic concepts and theories related to E-commerce systems and databases. Then perform database performance analysis using several parameters, such as response time, throughput, and resource usage. The results of the study show that database performance on E-commerce systems is still adequate, but there are still some problems that need to be fixed, such as increasing response times and using resources more efficiently. Therefore, continuous improvement is needed so that database performance on the E-commerce system is optimized so that it can provide a better shopping experience for users and increase profits for business owners.